2016
DOI: 10.1016/j.yexcr.2016.03.022
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of hTERT and Cyclin D1 transcription via PI3K/Akt and TGF-β pathways in MCF-7 Cancer cells with PX-866 and Raloxifene

Abstract: Human telomerase reverse transcriptase (hTERT) is the catalytic and limiting component of telomerase and also a transcription factor. It is critical to the integrity of the ends of linear chromosomes and to the regulation, extent and rate of cell cycle progression in multicellular eukaryotes. The level of hTERT expression is essential to a wide range of bodily functions and to avoidance of disease conditions, such as cancer, that are mediated in part by aberrant level and regulation of cell cycle proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Its activation seems to be more frequent in thyroid cancer types with poor differentiation, suggesting that telomerase activation may contribute to (or be associated with) more aggressive behavior of thyroid cancer [43]. Given the regulation of hTERT expression by p53 and other mechanisms [44, 45], we further examined the synergistic effect of p53 reactivation and PI3K/Akt pathway inhibition on hTERT expression. Our results not only showed that BKM120 and Prima-1 Met synergistically down-regulated hTERT promoter activity and its expression, but also demonstrated such down-regulation was mediated by decreased CFSF4 expression and its binding to the promoter region of hTERT.…”
Section: Discussionmentioning
confidence: 99%
“…Its activation seems to be more frequent in thyroid cancer types with poor differentiation, suggesting that telomerase activation may contribute to (or be associated with) more aggressive behavior of thyroid cancer [43]. Given the regulation of hTERT expression by p53 and other mechanisms [44, 45], we further examined the synergistic effect of p53 reactivation and PI3K/Akt pathway inhibition on hTERT expression. Our results not only showed that BKM120 and Prima-1 Met synergistically down-regulated hTERT promoter activity and its expression, but also demonstrated such down-regulation was mediated by decreased CFSF4 expression and its binding to the promoter region of hTERT.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HKR3 inhibited the expression of hTERT and decreased telomere activity in early cancer [17]. Inhibition of hTERT has been reported to inhibit cyclin activity [26]. Therefore, the correlation between hTERT, HKR3 and cell cycle factors can be confirmed.…”
Section: Discussionmentioning
confidence: 88%
“…Downregulation of PEA15 and survivin by EGCG has been shown to occur via reduced phosphorylation of Akt in U87 cells (53). In addition, downregulation of telomerase expression was also found to occur by suppression of phosphorylation of AKT (84). Moreover, GRP78 has been reported to be responsible for tamoxifen resistance in breast cancer which is regulated by phosphorylated AKT (85).…”
Section: ) Pea15mentioning
confidence: 97%